COGNITIVE-BEHAVIORAL THERAPY IN THE TREATMENT OF BINGE EATING DISORDER: EVIDENCE, LIMITATIONS, AND PERSPECTIVES (REMUNOM, 2026)
Binge Eating Disorder (BED) is one of the most prevalent eating disorders, characterized by recurrent episodes of uncontrolled food intake. Despite its significant clinical and psychosocial impact, there is still a shortage of national studies that integrate recent evidence on effective psychotherapeutic strategies for this condition. In this context, the present qualitative literature review aims to critically analyze the contributions of Cognitive Behavioral Therapy (CBT) in the treatment of BED, highlighting its theoretical foundations, intervention techniques, and most up-to-date empirical evidence. The literature review included scientific articles, dissertations, theses, and clinical manuals published between 2010 and 2023, with an emphasis on publications indexed in international and national databases. The results indicate that CBT is the psychotherapeutic intervention with the greatest empirical support, especially because it promotes cognitive restructuring, emotional regulation, and the modification of maladaptive eating patterns. However, the analysis revealed clinical and contextual limitations and tensions, including challenges related to patient adherence, the lack of longitudinal studies, and insufficient research conducted within Brazilian public health settings. It is concluded that CBT, although internationally established as the treatment of choice for EDs, requires further investigation that considers cultural specificities, inequalities in access to mental health care, and the training of qualified professionals in Brazil. The article therefore contributes by offering a critical and contextualized synthesis of the effectiveness and challenges of CBT, broadening the scientific and clinical debate on interventions in eating disorders in the Brazilian context.